2021
DOI: 10.1158/0008-5472.can-20-2009
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Secretion of PKCδ Exerts Tumorigenic Function via Stimulation of ERK1/2 Signaling in Liver Cancer

Abstract: Expression of human protein kinase C delta (PKCδ) protein has been linked to many types of cancers. PKCδ is known to be a multifunctional PKC family member and has been rigorously studied as an intracellular signaling molecule. Here we show that PKCδ is a secretory protein that regulates cell growth of liver cancer. Full-length PKCδ was secreted to the extracellular space in living liver cancer cells under normal cell culture conditions and in xenograft mouse models. Patients with liver cancer showed higher le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…The cationic amino acid clusters closely resemble the NLS of intracellular proteins[ 68 ]. In fact, extracellular NLS-containing proteins, such as importin α1, huRNP-K, and PKCδ are detected at the cell surface of human cells[ 9 , 69 , 70 ]. These extracellular NLS-containing proteins are more likely to be located at the cell surface by binding to HSPGs.…”
Section: Subcellular Localizations and Functions Of Pkcδmentioning
confidence: 99%
See 3 more Smart Citations
“…The cationic amino acid clusters closely resemble the NLS of intracellular proteins[ 68 ]. In fact, extracellular NLS-containing proteins, such as importin α1, huRNP-K, and PKCδ are detected at the cell surface of human cells[ 9 , 69 , 70 ]. These extracellular NLS-containing proteins are more likely to be located at the cell surface by binding to HSPGs.…”
Section: Subcellular Localizations and Functions Of Pkcδmentioning
confidence: 99%
“…Furthermore, glypican3, a liver cancer-specific HSPG, was identified as a receptor for cell surface PKCδ[ 71 ]. Both Cheng et al [ 72 , 73 ] and we showed that GPC3 regulates the activation of insulin-like growth factor 1 receptor (IGF1R)[ 9 ]. In fact, we found that extracellular PKCδ induces activation of IGF1R via association with GPC3 and its downstream signaling molecules, such as ERK1/2 and STAT3.…”
Section: Subcellular Localizations and Functions Of Pkcδmentioning
confidence: 99%
See 2 more Smart Citations
“…Regulating several intracellular signaling pathways, PKC has been linked to the carcinogenesis of many malignancies, including prostate cancer (Ratnayake et al, 2021[ 35 ]). Within the family of PKC isoforms, PKCδ plays a critical role in regulating apoptosis and tumor progression (Yamada et al, 2021[ 40 ]). PKCδ is a serine-threonine kinase with opposing functions that depend on its localization, tyrosine phosphorylation and the presence of other pro- and anti-apoptotic signaling molecules.…”
Section: Introductionmentioning
confidence: 99%